PENGARUH LABELISASI HALAL TERHADAP MINAT BELI (STUDI PADA KONSUMEN PIZZA HUT KOTA MEDAN) - Aminuddin Harahap (Universitas Islam Islam Sumatera Utara, 2018)
This study aims to determine how is the effect of halal label to buying interest of Pizza Hut consumers at Medan City. The study is employing quantitative method in which survey was used as an instrument for data collection. The collected data was analyzed by using simple linear regression analysis. The respondent of the study was divided into two categories; the consumers with a minimum requirement of 18 years old and for those who never consumed Pizza Hut food. In this research, data analysis with simple linier regression analysis method showed that halal labelisasi positively effected to consumer buying interest. Based on the results of simultaneous test (Test F) that the labeling of halal effected positively and signifikan. R value of 0.857 means halal labeling (X) had an influence of 73.4% of consumer buying interest, and the rest influenced by undescribed variables in this regression model.